Analysis of Determinants of Public Health Service Utilization in the Working Area of the West Ampana Health Center, Tojo Una-Una Regency - Amita, Tri Mayang; Rajindra, Rajindra; Amalinda, Finta (Rifa'Institute, 2026)
Introduction: Low utilisation of public healthcare services remains a persistent challenge influenced by multiple individual and environmental factors. The Community Health Centre (Puskesmas), as a primary healthcare facility, plays a critical role in improving community health status. Key determinants such as accessibility, culture, family support, and perceptions of illness and services are considered central to understanding patterns of healthcare utilisation. Objective: This study aims to identify and analyse the determinants of public healthcare service utilisation in the working area of the West Ampana Community Health Centre, Tojo Una-Una Regency. Method: A quantitative analytical approach was employed involving 99 respondents selected using Slovin's formula. Data were collected through structured questionnaires and analysed using univariate, bivariate, and multivariate analysis with SPSS. Results and Discussion: Significant relationships were found between accessibility, culture, family support, perceptions of illness and services, and healthcare utilisation (p < 0.005). Multivariate analysis revealed that accessibility and culture were the most dominant influencing factors, indicating that structural and sociocultural barriers substantially limit community engagement with available health services. Conclusion: Healthcare service utilisation is shaped by accessibility, culture, family support, and perceptions of illness and services. Improving culturally sensitive approaches and health education by healthcare workers are essential strategies to enhance service utilisation and optimise primary healthcare engagement at the community level